Maniac Magee : a novel - Spinelli, Jerry (Boston : Little, Brown, 1990)
After his parents die, Jeffrey Lionel Magee's life becomes legendary, as he accomplishes athletic and other feats which awe his contemporaries.
NEWB
BG
PW
NOT
HBFF
SLJ
Keywords: Human relations -- Fiction; Death -- Fiction; Orphans -- Fiction; Homeless people -- Fiction; Race relations -- Fiction; Homeless persons -- Fiction; Athletes -- Fiction